Synodalność we wczesnym chrześcijaństwie (V Międzynarodowa Konferencja Patrystyczna, KUL, Lublin, 7-9.10.2025) - Głowacki, Paweł (Vox Patrum, 2025)
Report from the 5th International Patristic that took place on oCtober 7-9, 2025 at the John Paul II Catholic University of Lublin. The subject was: Synodality in the Early Church.